THE INFLUENCE OF THE USE OF RECYCLED GYPSUM ON THE PROPERTIES OF GYPSUM PRODUCTS IN LABOR CONDITIONS - Hana Sekavová; Jakub Herrmann; Zdeněk Prošek; Miroslav Nyč; George Karra’a (Acta Polytechnica CTU Proceedings)
The article presents the first results from research, which is deal with recycling of plaster boards and use of the resulting material. The research is carried out within the project MPO Trio c. FV30359 “Recyklace sádrokartonových desek a nová materiálová využití s pridanou hodnotou – GIPSRec”. The plasterboards are produced of stucco, which is calcinated of Flue Gas Desulfurization Gypsum (FGD Gypsum). There is possibility to replace a part of this stucco with recycled material. There is opportunity for saving costs for production. The question how this utilization can change the properties of the products is very important and it is necessary to find the possible improvement or deterioration. This is the objective of this research. The effect on properties was monitored on the samples which was prepared of only pure stucco and of stucco with part of recycled material. There was observed water ratio (splash test), setting times, volume changes, flexural strength, compressive strength and elasticity module.